Variant of adynamic bone disease in hemodialysis patients: Fact or fiction? - Rocha, Lillian Andrade da [UNIFESP] (2006)
Background: Adynamic bone disease is a type of renal osteodystrophy characterized by low bone turnover and paucity of bone cells. It was proposed that a new type of this disease featuring high osteoclastic resorption without parathyroid hormone stimulus and designated adynamic bone disease variant occurs in hemodialysis patients. the present study is designed to evaluate the frequency and characteristics of both diseases in a large series of bone biopsy specimens. Methods: We reviewed 1,160 bone biopsy specimens from hemodialysis patients. Specimens in which adynamic bone disease was diagnosed were selected and categorized as classic or variant based on osteoclastic surface. Results: in 218 bone biopsy specimens (18.8%), adynamic bone disease was identified, whereas the variant form was identified in 35 specimens (38.8%). Biopsy specimens categorized as the variant form were from patients who were younger and had greater phosphorus and parathyroid hormone levels. Histologically, the variant form presented greater osteoid volume, fibrosis volume, osteoid surface, osteoblast surface, and eroded surface. Similarly, values for all dynamic parameters were greater in the variant group. Osteoclastic surface correlated with phosphorus level, parathyroid hormone level, and osteoblast surface. Age and osteoblast surface were identified as independent determinants of the variant form. Conclusion: Adynamic bone disease variant seems to occur in younger hemodialysis patients with greater levels of parathyroid hormone, which acts on cell-covered bone surfaces. It probably is a transitional phase from low- to high-turnover status, rather than a true entity within the spectrum of renal osteodystrophy.